Design, synthesis, and antitumor study of a series of novel 1-Oxa-4-azaspironenone derivatives. (15th October 2022) - Yin, Honglu; Chen, Yuepeng; Zhong, Qiu; Zheng, Shilong; Wang, Guangdi; He, Ling
Graphical abstract: Abstract: A series of 1-oxa-4-azaspiro[4, 5]deca-6, 9-diene-3, 8-dione derivatives containing structural fragments of conjugated dienone have been synthesized previously by our group, however the Michael addition reaction between conjugated dienone and nucleophilic groups in the body may generate harmful and adverse effects. To reduce harmful side effects, the authors started with p-aminophenol to make 1-oxo-4- azaspirodecanedione derivatives, then utilized the Michael addition and cyclopropanation to eliminate α, β unsaturated olefinic bond and lower the Michael reactivity of the compounds in vivo for optimization. At the same time, heteroatoms are put into the molecules in order to improve the hydrophilicity of the molecules and the binding sites of the molecules and the target molecules, establishing the groundwork for improved antitumor activity. The majority of the compounds had moderate to potent activity against A549 human lung cancer cells, MDA-MB-231 breast cancer cells, and Hela human cervical cancer cells. Among them, the compound 6d showed the strongest effect on A549 cell line with IC50 of 0.26 μM; the compound 8d showed the strongest cytotoxicity on MDA-MB-231 cell line with IC50 of 0.10 μM; and the compound 6b showed the strongest activity on Hela cell line with IC50 of 0.18 μM.